Stereoselective Syntheses of Tetrahydropyrans Applications to the Synthesis of (+)-Leucascandrolide A, (+)-Dactylolide and (±)-Diospongin A - Lee, Kiyoun (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
In his thesis, Kiyoun Lee describes his studies into tandem and organocatalytic oxa-conjugate addition reactions for the synthesis of complex tetrahydropyrans (THP). Readers gain insight into the new methods Lee employs for the synthesis of biologically interesting natural products including (+)-leucascandrolide A, (+)-dactylolide, and (±)-diospongin A. The reactions Lee investigates are applicable to a broad range of substrates and proceed with excellent stereoselectivity. Moreover, the methodologies allow the synthesis of a wide range of THP-containing compounds. The development of reactions, such as those discussed by Lee, has the potential to impact natural product synthesis, pharmaceutical development and chemical biology.  .